Espaços Urbanos de Lazer: Praças Públicas e Dinâmicas Socioespaciais em Uberlândia (MG) - Lucas, Fabricio da Mata (2022)
The present issue brings up a relevant reflection concerning the use of intra-urban space within the scope of current cities when considering public spaces and their interface with leisure. This research observes the importance of public open spaces in the consolidation of cultural and/or sports activities that favor the quality of life in cities. The implications that influence people's daily lives and the activities carried out in their available time are relevant, with emphasis on the forms of consumption of parks and public squares, the latter being vital for the well-being in cities, once they are more present in the intra-urban space. From this perspective, this study lists a reflection on the reality of the city of Uberlândia (MG). In the city, there is a representative expansion of the urban fabric and the population contingent, with just over 700,000 inhabitants in 2021, having no balanced distribution of the open spaces of public squares, with greater concentration in the surroundings of neighborhoods that are part of or close to the Central Sector. The thesis aims to analyze the public spaces intended for leisure in the city of Uberlândia (MG), specifically about the open spaces of public squares. The main focus is structured from two eminently theoretical moments and other three that refer to the analysis of the organization of leisure activities in the public open spaces of the city. In the theoretical scope, the present study initially presents the existing dynamics within the urbanization process, taking into account the agents that act in the production of intra-urban space. It is necessary to visualize the aspects that refer to territorial growth, with the discontinuities present in the urban fabric, the new centralities, and the intrinsic processes of socio-spatial segregation and social exclusion. The research analyzes the expansion of contemporary Brazilian cities, visualizing the growth of interior and medium-sized cities, intending to insert the city that guides this discussion, in addition to integrating leisure in the context and current urban projects. Subsequently, the study resumes the analysis about the consolidation of leisure in society and then addresses the forms of appropriation and consumption of space, with an approach around public spaces. To analyze the organization of leisure activities in the city, the consolidation of public spaces and existing equipment is considered, followed by the panorama of related public policies and, specifically, the open spaces of public squares. Then, the research highlights information provided by residents of different neighborhoods in the city about their leisure options and ways of using public squares. In the last moment, this study observes how the appropriation of the open spaces of the squares occurs, considering the reality of some squares present in both elite and peripheral areas of the city. It is noteworthy that the open spaces of the squares are the most democratic spaces, subject to contradictions and possibilities of social interaction in the moments of leisure of the city dwellers.